Iatrogenic colonoscopic perforations: a review of 8 158 patients - KAZANAVIČIUS, Darius; SAMALAVIČIUS, Narimantas Evaldas (Acta medica Lituanica, 2012)
Purpose. The aim of the study is to determine the incidence of perforation after colonoscopy (CP) in our institution, and to evaluate the endoscopic information, clinical presentation, diagnosis workup, intra-operative findings, management and outcomes of patients with CP. Methods. All colonoscopies performed between January 2005 and December 2011 at the Oncology Institute of Vilnius University, Lithuania, searched for colonoscopic perforations. Medical records of all CP patients were reviewed. Incidence of CP, patients’ characteristics, endoscopic information, intra-operative findings, management and outcomes were analyzed. Results. A total of 8,158 colonoscopies (7,467 diagnostic and 691 therapeutic) were performed in our hospital over a 7-year period. Five patients (0.061%) had CP: 2 from diagnostic colonoscopy (incidence 0.027%) and 3 from therapeutic one (0.43%). In two cases, perforation was noticed by the endoscopist through visualization of extra-intestinal tissue during the procedure. Other perforations (n = 3, 60%) were diagnosed after the procedure. The most consistent symptom was abdominal pain followed by tenderness, abdominal distension, leukocytosis. The most common site of perforation was in the sigmoid colon (n = 3, 60%). Perforations were caused by direct trauma from the endoscope (n = 2, 40%) and endoscopic polypectomy (n = 3, 60%). All patients with CP underwent surgical management: primary repair. The mortality rate was 0% and the postoperative complication rate was 40%. Conclusions. CP is a serious but rare complication of colonoscopy. Incidence of CP was 0.061%. Therapeutic procedures have a higher perforation risk than diagnostic procedures. The sigmoid colon is the area at the greatest risk of perforation. Surgery is still the mainstay of CP management.